Epidemiologic comparison of the first and second waves of coronavirus disease epidemics in Babol, North of Iran - Seyed Farzad Jalali; Mostafa Ghassemzadeh; Simin Mouodi; Mostafa Javanian; Mehdi Akbari Kani; Reza Ghadimi; Ali Bijani (Babol University of Medical Sciences, 2020)
Background: A few studies compared the epidemiologic features of the first and second waves of coronavirus disease 2019 (COVID-19) outbreak. This research was carried out to compare the 1st and the 2nd waves of the epidemics in the northern Iran. Methods: In this observational research, demographic, clinical and laboratory characteristics of the patients with COVID-19, admitted to four government hospitals affiliated to Babol University of Medical Sciences during the 1st and the 2nd waves of COVID-19 epidemics have been compared. The period from May 21, 2020 to September 21, 2020 was considered as the second wave of the epidemics while from February 19, 2020 to May 20, 2020, as the first wave of the outbreak in this region. Results: Out of 6691 total hospitalized cases, 4374 (65.37%), including 1532 (49.6%) people in the first wave and 2842 (78.9%) in the second wave had RT-PCR test for disease confirmation. Among those who were examined with RT-PCR test, 2322 patients (53.1%) including 728 (31.4%) persons in the first wave and 1594 (68.6%) in the second wave were positive for SARS-CoV-2 RNA. 414 (56.9%) of the confirmed cases in the first wave and 767 (48.1%) in the second wave were males (p<0.001). Gastrointestinal symptoms were more incidental in the second wave of the disease. However, severe respiratory conditions were more common during the first wave (p<0.001). Crude mortality rate was lower in the second wave of the outbreak (p<0.001). Conclusion: Different epidemiologic characteristics were found in the second wave of COVID-19 outbreak in comparison with the first wave of the epidemics in northerrn Iran.